UPAYA PEMBERDAYAAN SISWA SEBAGAI KADER “PEDULI’ (PENGENDALIAN DAN ELIMINASI) DBD PADA SISWA SMPN 41 KOTA PADANG - Masrizal Masrizal; Dien Dien; Muhammad Alfarezi; Muhammad Iqbal; Fitri Yusya; Devy Shintya (BULETIN ILMIAH NAGARI MEMBANGUN, 2022)
Service activities based on the realization of a healthy school environment are carried out by forming and empowering a larva monitoring team or jumantik in schools. This activity aims to create a school that is healthy and free from mosquito larvae, especially the Aedes Aegypti mosquito which is a vector of dengue fever. The activity was carried out by carrying out a pretest and posttest, counselling and also socialization to school residents about DHF and also jumantik. After equalizing perceptions about jumatiK, a member of the jumantik team will be recruited who will be tasked with monitoring larvae, eradicating mosquito nests, as well as recording and reporting on the presence of mosquito larvae in the area of SMPN 41 Padang City. There is a significant difference in the average level of knowledge and attitudes of students at SMPN 41 Padang before and after counselling and providing material regarding the larva monitoring team. This shows that the counselling provided can affect the level of knowledge, attitudes and behaviour of students regarding larva monitoring and dengue fever for the better. A Jumantik team has been formed in each class. Hopefully, the team will do well in the future.